2020
DOI: 10.11591/edulearn.v14i1.14090
|View full text |Cite
|
Sign up to set email alerts
|

Sociolinguistics perspectives on gender patterns in instagram

Abstract: This article focused on the the gender patterns that were found in the social media Instagram based on the sociolinguistics point of view. There were two research questions were arisen what types of the gender patterns that were found in the social media Instagram based on the sociolinguistics and the factors of the difference language used based on gender in social media Instagram. Uses and Gratifications Theory (UGT) was used to analyze the data. The data was taken from all of component of the sociolinguisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(15 reference statements)
0
0
0
1
Order By: Relevance
“…Park et al (2016) pinpointed the differences in topics associated with both genders: female Facebook users tended to talk more about social-related topics (e.g., friends and family), whereas the male users focused more on discussing objects or giving arguments, further complemented with swearing and expression of anger. In the case of Instagram, Yuliani et al (2020) observed similar findings in that women were more likely to share personal stories, in contrast to men who shared less personal content. They also revealed that females used more implicit language features (e.g., hedging expressions) than males who relied on direct and explicit language (e.g., swear words).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Park et al (2016) pinpointed the differences in topics associated with both genders: female Facebook users tended to talk more about social-related topics (e.g., friends and family), whereas the male users focused more on discussing objects or giving arguments, further complemented with swearing and expression of anger. In the case of Instagram, Yuliani et al (2020) observed similar findings in that women were more likely to share personal stories, in contrast to men who shared less personal content. They also revealed that females used more implicit language features (e.g., hedging expressions) than males who relied on direct and explicit language (e.g., swear words).…”
Section: Introductionmentioning
confidence: 62%
“…The difference in linguistic features can result from how influencers build intimacy with their followers. The use of second-person pronouns among female influencers in contrast to the use of imperatives among males might indicate the indirect and direct nature of talk for both genders, respectively (Park et al, 2016;Yuliani et al, 2020). Female influencers possibly want the followers to construe the post as an 'invitation' to use the products, whereas the men consider it 'directives' for their viewers.…”
Section: Interpersonal Metafunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kajian ini akan mampu mendokumentasikan dan menginventarisasi berbagai hal yang berkaitan dengan perkembangan bahasa Sunda, khususnya pelestarian bahasa Sunda di kalangan milenial di Kabupaten Ciamis. Sosiolinguistik dapat dipahami sebagai cabang linguistik yang mengkaji relasi bahasa dengan masyarakat penggunanya (Li, 2014;Saddhono & Rohmadi, 2014;Wardhaugh & Fuller, 2015;Yuliani et al, 2020). Hal ini tidak terlepas dari dua disiplin ilmu sosial dan linguistik di dalamnya.…”
Section: Pendahuluanunclassified